EXPLAINING AUDIT REPORT LAG : THE INFLUENCE OF CEO SUCCESSION AND FIRM CHARACTERISTICS - Icih Icih; Ikka Rachmawati; Asep Kurniawan; Indah Umiyati; Sri Mulyati (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2025)
Recent research has suggested a connection between Corporate Sustainable Management (CSM) endeavors and the transparency of financial reporting, highlighting CSM's role in mitigating information disparities between corporations and stakeholders. As CSM activities increase, it is believed that the quality of reported profits also enhances, benefiting both the company and its stakeholders. This research investigates how the origin of CEO succession, company operational complexity, company age, and financial condition influence audit report lag, especially for manufacturing firms listed on the IDX between 2018 to 2022. The research involved a population of 163 companies, utilizing purposive sampling to select a sample of 142 companies, resulting in a dataset comprising 650 data points. Data analysis utilized logistic regression through SPSS version 25 and Microsoft Excel. This research adopts a quantitative methodology, drawing upon secondary data sourced from annual reports accessible via the Indonesian Stock Exchange's official website or the respective companies' websites. Findings indicate that CEO succession origin and company's financial condition positively influence audit report lag, whereas company operations complexity and company age exhibit a negative association with audit report lag.